2021
DOI: 10.3389/fneur.2020.635341
|View full text |Cite
|
Sign up to set email alerts
|

Enablers to Exercise Participation in Progressive Supranuclear Palsy: Health Professional Perspectives

Abstract: Background: People living with progressive supranuclear palsy (PSP) can experience considerable difficulties with movement, walking, balance, and oculomotor control. The role of exercises and physical activities in mitigating the motor and non-motor symptoms of PSP remains uncertain.Aims: The aim of this study was to identify the perspectives and beliefs of health professionals about the benefits, enablers, and barriers to participation in exercise and physical activity across the course of disease progression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Another barrier to receiving evidence‐based therapy is the parkinsonism subgroup. Little is known about how best to prevent falls in people with Progressive Supranuclear Palsy, Multiple System Atrophy, Cortico‐basal degeneration, and other forms of atypical parkinsonism 93,94 . We did not specifically evaluate the impact of deep brain stimulation (DBS) on falls; however patients undergoing DBS may share risk factors for falls with PD patients under medical management, including age, axial features, and disease duration 95 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another barrier to receiving evidence‐based therapy is the parkinsonism subgroup. Little is known about how best to prevent falls in people with Progressive Supranuclear Palsy, Multiple System Atrophy, Cortico‐basal degeneration, and other forms of atypical parkinsonism 93,94 . We did not specifically evaluate the impact of deep brain stimulation (DBS) on falls; however patients undergoing DBS may share risk factors for falls with PD patients under medical management, including age, axial features, and disease duration 95 .…”
Section: Resultsmentioning
confidence: 99%
“…92 Digital delivery of falls prevention interventions is a promising intervention for the future yet the systems supporting it are still under development. Another barrier to receiving 93,94 We did not specifically evaluate the impact of deep brain stimulation (DBS) on falls; however patients undergoing DBS may share risk factors for falls with PD patients under medical management, including age, axial features, and disease duration. 95 Novel targets, such as the pedunculopontine nucleus (and other areas) are being investigated as potential targets that might improve axial features and falls risk.…”
Section: Barriers To Falls Prevention In Pdmentioning
confidence: 99%
“…Physiotherapy interventions for PSP face challenges owing to the absence of clinical guidelines on exercise for this disease. Previous studies have emphasized the importance of early exercise for enhancing to strength and overall motor function, particularly before cognitive impairment occurs (Wittwer et al, 2019;Morris et al, 2021;Dale et al, 2023). Case 3 highlights the benefits of initiating physiotherapy during the early stages of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Adapting interventions to the individual needs, preferences, motivations, and involvement of caregivers is crucial for continued intervention at home and, promoting greater knowledge about the disease and coping mechanisms (Slade et al, 2019. Communication difficulties and cognitive impairment can limit social participation Morris et al, 2021), as observed during the COVID-19 interruption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation